Novel tridentate nitrogen donor as ligand in copper catalyzed ATRP of methyl methacrylate - Mittal, A.; Sivaram, S. (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
A tridentate ligand, BPIEP: 2,6-bis[1-(2,6-diisopropyl phenylimino) ethyl] pyridine, having central pyridine unit and two peripheral imine coordination sites was effectively employed in controlled/''living'' radical polymerization of MXU at 90 degrees C in toluene as solvent, (CuBr)-Br-I as catalyst, and ethyl-2-bromoisobutyrate (EBiB) as initiator resulting in well-defined polymers with polydispersities M-W/M-n <= 1.23. The rate of polymerization follows first-order kinetics, k(app) = 3.4 x 10(-5) s(-1), indicating the presence of low radical concentration ([P*] <= 10(-8)) throughout the reaction. The polymerization rate attains a maximum at a ligand-to-metal ratio of 2:1 in toluene at 90 degrees C. The solvent concentration (v/v, with respect to monomer) has a significant effect on the polymerization kinetics. The polymerization is faster in polar solvents like, diphenylether, and anisole, as compared to toluene. Increasing the monomer concentration in toluene resulted in a better control of polymerization. The molecular weights (M-n,M-SEC) increased linearly with conversion and were found to be higher than predicted molecular (M-n,M-Cal). However, the polydispersity remained narrow, i.e., <= 1.23. The initiator efficiency at lower monomer concentration approaches a value of 0.7 in 110 min as compared to 0.5 in 330 min at higher monomer concentration. The aging of the copper salt complexed. with BPIEP had a beneficial effect and resulted in polymers with narrow polydispersitities and higher conversion. PMMA obtained at room temperature in toluene (33%, v/v) gave PDI of 1.22 (Mn = 8500) in 48 h whereas, at 50 degrees C the PDI is 1.18 (Ma = 10,300), which is achieved in 23 h. The plot of In kapp versus 1/T gave an apparent activation energy of polymerization as (Delta E-app(not equal)) 58.29 KJ/mol and enthalpy of equilibrium (Delta H-eq(0)) to 28.8 KJ/mol. Reverse ATRP of MMA was successfully performed using AIBN in bulk as well as solution. The controlled nature of the polymerization reaction was established through kinetic studies and chain extension experiments. (c) 2005 Wiley Periodicals, Inc.
Keywords: 2; 6-bis [1-(2; 6-diisopropyl phenylimino) ethyl] pyridine (BPIEP); Activation energy; apparent rate constant; Atom transfer radical polymerization (ATRP); diphenylether; ethyl-2-bromoisobutyrate (EBiB); methyl methacrylate; polydispersity index (PDI); Toluene

Structure of poly(L-lactic acid)s prepared by the dehydropolycondensation of L-lactic acid with organotin catalysts - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The synthesis of low-molecular-weight (weight-average molecular weight < 45,000 g/mol) lactic acid polymers through the dehydropolycondensation of L-lactic acid was investigated. Polymerizations were carried out in solution with solvents (xylene, mesitylene, and decalin), without a solvent using different Lewis acid catalysts (tetraphenyl tin and tetra-n-butyldichlorodistannoxane), and at three different polymerization temperatures (143, 165, and 190 degrees C). The products were characterized with differential scanning calorimetry, size exclusion chromatography, vapor pressure osmometry, C-13 NMR, and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). The resulting polymers contained less than 1 mol % lactide, as shown by NMR. The number-average molecular weights were calculated from the ratio of the area peaks of ester carbonyl and carboxylic acid end groups via C-13 NMR. The stereosequences were analyzed by C-13 NMR spectroscopy on the basis of triad effects. Tetraphenyl tin was an effective transesterification catalyst, and the randomization of the stereosequence at 190 degrees C was observed. In contrast, the distannoxane catalyst caused comparatively less transesterification reaction, and the randomization of the stereosequences was slow even at 190 degrees C. The L-lactic acid and D-lactic acid isomers were added to the polymer chain in a small, blocky fashion. The MALDI-TOF spectra of poly(L-lactic acid) (PLA) chains doped with Na+ and K+ cations showed that the PLA chains had the expected end groups. The MALDI-TOF analysis also enabled the simultaneous detection of the cyclic oligomers of PLA present in these samples, and this led to the full structural characterization of the molecular species in PIA. (c) 2005 Wiley Periodicals, Inc.
Keywords: C-13 NMR; dehydropolycondensation; Lewis acid catalysts; MALDI; polymerization; randomization; stereosequence

Unfavorable coordination of copper with methyl vinyl ketone in atom transfer radical polymerization - Mittal, A.; Sivaram, S.; Baskaran, D. (Macromolecules, 2006)

Copolyesters based on poly(butylene terephthalate)s containing cyclohexyl and cyclopentyl ring: Effect of molecular structure on thermal and crystallization behavior - Sandhya, T. E.; Ramesh, C.; Sivaram, S. (Macromolecules, 2007)
In an effort to understand the role of molecular structure on the thermal properties of polyesters and copolyesters, the following polyesters were synthesized: poly(1,4-cyclohexane dimethylene terephthalate) (PCT), poly(butylene-1,4-cyclohexane dicarboxylate) (PBCD), poly (1,3-cyclopentane dimethylene terephthalate) (PCPDT), and poly(butylene-1,3-cyclopentane dicarboxylate) (PBCP). PCT and PCPDT are semicrystalline polymers with crystallization and melting temperatures higher than poly(butylene terephthalate) (PBT). However, PBCD and PBCP have lower glass transition temperature than PBT. From these homopolymers a series of poly(butylene-co-1,4-cyclohexane dimethylene terephthalate) (P(BT-co-CT )), poly(butylene terephthalate-co-1,4cyclohexane dicarboxylate) (P(BT-co-BCD)), poly(butylene-co-1,3-cyclopentylene dimethylene) (P(BT-co-CPDT)), and poly(butylene terephthalate-co-1,3-cyclopentane dicarboyxlate) (P(BT-co-PBCP)) random copolyesters were synthesized for the first time, and their cocrystallization behavior was investigated using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The copolymers were found to be statistically random and crystallized in all compositions. The P(BT-co-CT) and (P(BT-co-CPDT) copolyesters exhibited typical eutectic behavior in melting and crystallization, which indicated isodimorphic cocrystallization behavior. On the other hand, in the case of P(BT-co-BCD) and P(BT-co-PBCP) copolymers, the melting and crystallization temperatures showed linear dependency with composition, indicating isomorphic-like crystallization behavior.

High-temperature, polymer-graphite hybrid composites for bipolar plates: effect of processing conditions on electrical properties - Radhakrishnan, S.; Ramanujam, B. T. S.; Adhikari, Arindam; Sivaram, S. (Journal of Power Sources, 2007)
High-temperature thermoplastic-graphite composites are prepared using polyphenylene sulfide (PPS) and polyether sulfone (PES) containing natural graphite powder. All samples are prepared by high pressure compaction and heating to high temperatures. The effect of a third additional conducting component on the electrical resistance of these composites is studied. A low resistance of the order of 0.1 Omega can be obtained even for a graphite concentration of 50% by addition of the third component. The effect of a mixing/blending technique on the anisotropy of conductivity is investigated. Solution blending of PES with graphite leads to lower anisotropy values than powder mixing and compression moulding. The samples when exposed continuously to a working temperature of 100 degrees C give a small but significant reduction in electrical resistance. X-ray diffraction studies on composites prepared by different techniques indicate that there is restructuring and crystallite re-orientation of the graphite phase in the samples. A large reduction in the crystallite size is observed for samples prepared by solution blending while re-orientation occurs after heat treatment. The changes in electrical properties can be correlated with these structural transformations in the composites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bipolar plates; conducting polymer; fuel cell; graphite composites; hybrid materials; polyether sulfone; polypherylene sulfide

Polymerization of ethylene to branched poly(ethylene)s using ansa-eta(5)-monofluorenyl cyclohexanolato zirconium(IV) complex/methylaluminoxane - Rajesh, A.; Sivaram, S. (Polymer Bulletin, 2011)
ansa-eta(5)-Monofluorenyl cyclohexanolato zirconium complex 3 was shown to be active for the polymerization of ethylene when activated with methylaluminoxane (MAO) at 5 bar. Up to a polymerization temperature of 40 A degrees C, 3/MAO resulted in linear poly(ethylene)s with saturated chain ends. However, at polymerization temperatures of 60, 80, and 100 A degrees C, a mixture of branched poly(ethylene)s, linear alpha-olefins and long chain alkanes was obtained. The poly(ethylene)s produced at 80 and 100 A degrees C exhibited a bimodal molecular weight distribution indicative of multiple active species. Very high molecular weight (M (v) > 5 x 10(5)) linear poly(ethylene)s were obtained using 3/MAO at 25 A degrees C.
Keywords: ansa-Monofluorenyl complex; Bimodal MWD; Branched poly(ethylene)s; Ethylene polymerization; Methyl aluminoxane

Polymerization of ethylene using amido functional half-sandwich complexes of group 4 metals - Rajesh, A.; Sivaram, S. (Polymer Engineering and Science, 2011)
Ligands (C(13)H(9))(2,6-R(2)C(6)H(3)NH)SiPh(2) [R = (i)Pr (2a), Me (2b)] were synthesized by single deprotonation of the amino group in 2,6-dialkylanilines with n-BuLi at -78 degrees C followed by reaction with fluorenyl diphenyl silyl chloride [FluSi(Ph(2))Cl]. Single crystal X-ray diffraction studies revealed different geometries around the nitrogen atom for the two compounds. Titanium and zirconium complexes (3a-3d) were prepared by double deprotonation of the ligands with n-butyl lithium (n-BuLi) followed by reaction with the respective metal chlorides, MCl(4) (THF)(2). Polymerization of ethylene was performed using these complexes as catalyst precursors along with methylaluminoxane (MAO) as an activator at 5 bar pressure. Complexes 3a-3d/MAO exhibited moderate catalyst activities for polymerization of ethylene and resulted in high molecular weight linear poly(ethylene)s (M(v) > 4 3 10(5) g/mol). Catalyst activities were much lower when compared to similar N-alkyl substituted complexes presumably due to the resonance effect of the aromatic group on the amido nitrogen. POLYM. ENG. SCI., 51:2103-2108, 2011. (C) 2011 Society of Plastics Engineers

Reactive polymers bearing styrene pendants through selective anionic polymerization of 4-vinylbenzyl methacrylate - Mohan, Y. Murali; Raghunadh, V.; Sivaram, S.; Baskaran, D. (Macromolecules, 2012)
Selective anionic polymerization of 4-vinylbenzyl methacrylate at methacrylate site has been achieved using resonance stabilized anionic initiators such as 1,1-diphenylhexyllithium (DPHLi) and tritylpotassium (TritylK) in tetrahydrofuran (THF) at -78 degrees C. Polymerization proceeded selectively through methacrylate functionality of the monomer in a controlled manner and produced polymers and copolymers with narrow molecular weight distribution at low temperatures (<=-40 degrees C). H-1 NMR of the polymer showed the presence of styrene pendants in every monomeric repeating unit. The polymerization results confirm that the resonance stabilized carbanions with an optimum pK(a) (30 <= pK(a) <= 32) of their conjugate acids such as DPHLi and TritylK do not react with styrene functionality at 78 degrees C. The selective initiation without cross-linking is attributed to the differences in the electronegativity between polar methacrylate and styrene functionalities and an attenuation of initiator reactivity at low temperature. Poly(4-vinylbenzyl methacrylate) and its copolymers with the vinyl pendant in close proximity with ester linkage are very reactive and unstable, readily undergoing cross-linking in solution or in solid state with or without a radical initiator.

Sustainable materials based on aliphatic polyesters: teaching old chemistry some new tricks - Sivaram, S. (Current Science, 2013)

High molecular weight polylactic acids by polyesterification using diisopropylcarbodiimide (DIPC) and 4-(dimethylamino) pyridinium ptoluene sulfonate (DPTS) - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Polymer Bulletin, 2015)
High molecular weight poly(l-lactic acid) has been prepared from the corresponding functionally terminated oligomers employing a polyesterification method at room temperature using diisopropylcarbodiimide and 4-(dimethylamino) pyridinium-p-toluene sulfonate. Self-condensation of hydroxyl and carboxylic acid-terminated poly(l-lactic acid) oligomers (M (n) : similar to 1,000) resulted in polymers with high molecular weights (M (n) > 45,000) under mild conditions. End-group analysis by MALDI-TOF provided evidence for N-acylurea formation in the product under the reaction conditions employed.

Synthesis of functional polymers of polar and nonpolar monomers by living and/or controlled polymerization - Chowdhury, S. R.; Sivaram, S. (Functional polymers: design, synthesis, and applications, 2017)

Bhaskar Dattatraya Kulkarni (1949-2019) - Kumar, V. Ravi; Sivaram, S. (Current Science, 2019)